A radical agenda for enabling organisation transformation through work-applied learning. Issue 1 (1st March 2016) - Critten, Peter
Abstract : Purpose: The purpose of this paper is to challenge how we have traditionally thought about organisations and introduce two frameworks to enable us to understand how change in organisations might be facilitated better. Design/methodology/approach: The paper discusses organisations as complex adaptive systems and uses complexity theory to inform two new frameworks for facilitating organisational learning and change. Findings: In order for organisational learning to occur we need to change our mind-set of how we see organisations and to think of learning not just as individual but also as generative "communicative action" that emerge out of collaborative relationships. Research limitations/implications: The frameworks proposed are grounded in organisational learning literature and the experience of the author. The proposed agenda for organisational learning has yet to be acted upon and evaluated. Practical implications: The frameworks can be used to enhance understanding of learning and change in organisations. The agenda for enabling organisational transformation identifies key steps to put the ideas developed in the paper into practice. Social implications: The approach advocated for use within organisations is one of empowerment and collaboration rather than top down direction. Originality/value: The paper introduces new frameworks and a practical agenda to bring about organisational transformation through work-applied learning.